Structural Colors on Al Surface via Capped Cu-Si3N4 Bilayer Structure - Rahman, M. A.; Kim, Dongkyu; Arora, Deepshikha; Huh, Joo-Youl; Byun, Ji Young (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Tunable structural colors have a multitude of applications in the beautification of mobile devices, in the decoration of artwork, and in the creation of color filters. In this paper, we describe a Metal-Insulator-Metal (MIM) design that can be used to systematically tune structural colors by altering the thickness of the top metal and intermediate insulator. Cu and Si3N4 were selected as the top metal and intermediate insulator layers, respectively, and various reflection colors were printed on Al. To protect the Cu surface from scratchiness and oxidation, a number of capping layers, including SiO2, LPSQ, PMMA, and the commercially available clear coat ProtectaClear, were applied. In addition to their ability to protect Cu from a humid environment without deteriorating color quality, ProtectaClear and LPSQ coatings have minimal angle dependency. Furthermore, a bilayer of PMMA/SiO2 can protect the Cu surface from the effects of humidity. In addition, the PMMA/SiO2 and ProtectaClear/SiO2 bilayers can also protect against corrosion on the Cu surface. The colors can be tuned by controlling the thickness of either the metal layer or intermediate insulator layer, and vivid structural colors including brown, dark orange, blue, violet, magenta, cyan, green-yellow, and yellow colors can be printed. The measured dielectric functions of Cu thin films do not provide any evidence of the plasmonic effect, and therefore, it is expected that the obtained colors are attributed to thin-film interference.